Viabilidade econômica de um sistema de energia solar fotovoltaica residencial: estudo de caso - AMARAL, Breno da Silva (2023)
The use of photovoltaic solar energy has become increasingly common due to the worldwide trend towards the use of renewable energies, respect for the environment and sustainability. Society is turning its eyes to intensify the use of renewable resources and the preservation of the environment and, nevertheless, the use of clean energies are increasingly part of the daily life of the world scenario. The objective of this work is to perform an economic feasibility analysis of a photovoltaic solar energy system through a study in a family residence with 220 m2 of built area, located in a middle/upper class condominium in the city of Belém of Pará. In the building, 20 plates of 550W of power and 5 inverters of 2,000W were installed in the building in order to generate energy, injecting it into the distribution system of the concessionaire to deduct the energy consumed, thus reducing the costs of the energy bill. A reference scenario was established, without the photovoltaic system installed and considering the value of the integral energy bills. After this parameter was created, three more scenarios were created. In scenario 1, the installation of the system with financing in 24 installments was considered, in scenario 2, the financing was considered in 48 installments, and finally, scenario 3 with financing in 60 installments. When these scenarios were compared, results were found in order to prove the feasibility of installing this type of system to reduce the monthly cost with electricity bills.